2013
DOI: 10.1016/j.foodchem.2012.12.033
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary carnosic acid on the fatty acid profile and flavour stability of meat from fattening lambs

Abstract: El artículo seleccionado no se encuentra disponible por ahora a texto completo por no haber sido facilitado todavía por el investigador a cargo del archivo del mismo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
80
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(87 citation statements)
references
References 33 publications
5
80
0
2
Order By: Relevance
“…Thus, our study supports the finding that dietary CA stimulated the biosynthesis of aldehydes (i.e. volatile species from lipid autoxidation) in selected tissues of lambs (Morán et al, 2013;Rozbicka-Wieczorek et al, 2016c). On the other hand, lower levels of CA (≤ 0.6 g · kg −1 ) stimulated an antioxidant effect in tissues closer to that observed in lambs fed diets supplemented with vitamine E (Morán et al, 2013).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Thus, our study supports the finding that dietary CA stimulated the biosynthesis of aldehydes (i.e. volatile species from lipid autoxidation) in selected tissues of lambs (Morán et al, 2013;Rozbicka-Wieczorek et al, 2016c). On the other hand, lower levels of CA (≤ 0.6 g · kg −1 ) stimulated an antioxidant effect in tissues closer to that observed in lambs fed diets supplemented with vitamine E (Morán et al, 2013).…”
Section: Discussionsupporting
confidence: 89%
“…It was recently shown that diet enriched with Se-compounds and CA (both with antioxidative properties) modifies ruminal microbiota and hence FAs metabolism in the rumen (Morán et al, 2013;Birtić et al, 2015). As a consequence, the addition of dietary Se-compounds and/or CA affects FAs profile and levels of amino acids in the rumen and has a significant influence on biosynthesis of volatile compounds and concentrations of FAs, cholesterol and amino acids in lamb tissues (Miltko et al, 2016;Rozbicka-Wieczorek et al, 2016a,b,c).…”
Section: Introductionmentioning
confidence: 99%
“…3 The concentration sum of C14:0, C16:0, and C18:0. 4 The atherogenic index = (C12:0+4×C14:0+C16:0)/(MUFAs+n-6PUFAs+n-3PUFAs) (8). 5 The thrombogenic index = (C14:0+C16:0+C18:0)/0.5×MUFAs+0.5×n-6PUFAs+3×n-3PUFAs +n-3PUFAs/ n-6PUFAs) (8).…”
Section: Effect Of the Supplemented Diets On The Concentrations Of Sfmentioning
confidence: 99%
“…Numerous studies showed that diets supplemented with selenized yeast (SeY) or selenate (SeVI) change the contents of FAs, tocopherols, and malondialdehyde (MDA; a marker of the oxidative stress) in animal tissues (4,7,9,11,12). Interestingly, carnosic acid (CA; an antioxidant) is used as a preservative in food (8,13). Moreover, CA (a phenolic diterpene) can modify gut microbiota, resulting in changes of the ruminal bacterial metabolism (14).…”
Section: Introductionmentioning
confidence: 99%
“…The content of main groups of fatty acids (g 100 g −1 fat), the content ratios of PUFAs, MUFAs to SFAs, the content ratio of PUFAs n-3 to PUFAs n-6, and the content of cholesterol and phospholipids (g 100 g −1 fat)in milk of examined sheep breeds. ns: not significant, P > 0.5; SE: standard error of the mean; LSM: least square mean; SFAs: saturated fatty acids; MUFAs: monounsaturated fatty acids; PUFAs: polyunsaturated fatty acids; SMCFAs: fatty acids with 17 carbon atoms; LCFAs: fatty acids with 18 carbon atoms; C20-PUFAs: polyunsaturated fatty acids with 20 carbon atoms; n-3 / n-6: the concentration ratio of PUFAs n-3 to PUFAs n-6; Index T: thrombogenic index (C14 : 0 + C16 : 0 + C18 : 0/0.5 MUFA +0.5 PUFA n-6 +3 PUFA n-3 + n-3 / n-6); Index A: atherogenic index (C12 : 0 + 4xC14 : 0 + C16 : 0/ MUFA + PUFA n-6 and n-3) (Morán et al, 2013); TCh: total cholesterol; Pl: phospholipids.…”
Section: Resultsmentioning
confidence: 99%